2021
DOI: 10.1590/1809-4430-eng.agric.v41n1p9-18/2021
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Load Ventilation in Broiler Transport

Abstract: The characterization of ventilation during the transport of broiler chickens is essential for identifying and characterizing the potential problems of a convective heat flow and its effects on the welfare and the health and production conditions of the chickens. The objective of this study was to evaluate the ventilation patterns in two layout models of a live transport load: conventional (LC) and alternative (LA) with spacers placed between the chicken transport crates. Computational fluid dynamics (CFD) simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…A great heterogeneity in the enthalpy of the load can provide zones of high heat (thermal core), associated with the regions with Engenharia Agrícola, Jaboticabal, v.41, n.4, p.427-437, jul./aug. 2021 greater losses, about everything by animal deaths (Pinheiro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great heterogeneity in the enthalpy of the load can provide zones of high heat (thermal core), associated with the regions with Engenharia Agrícola, Jaboticabal, v.41, n.4, p.427-437, jul./aug. 2021 greater losses, about everything by animal deaths (Pinheiro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Poultry farming has a similar problem related to the flow of air and energy and the effect of thermal stress on transport vehicles. Studies have shown that the distribution of dead birds along the load during transport is not random; the points with the highest DOA rate correspond to the thermal zones with the highest energy content, known as thermal cores (Mitchell & Kettlewell 1998;Kettlewell et al, 1993;Kettlewell et al, 2001;Barbosa-Filho et al, 2009;Pinheiro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by improvements in vehicle design, using forced ventilation and air‐conditioning. The design of poultry crates and their spacing within the load is important for optimisation of ventilation, but more research is needed to define best options for various types of birds and climatic conditions (Bhatt et al., 2021 ; Pinheiro et al., 2021 ). It may also be possible to design ventilation or cooling systems linked to temperature sensors which can respond to different conditions within a load (Mitchell and Kettlewell, 2008 ; Ramadiani et al., 2021 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Transport is considered one of the most critical operations for animal welfare (Pinheiro et al, 2021). During transport, pigs are subjected to various stressors, such as mixing lots, deprivation of food and water, changes in the environment, vibrations and noise (Mota-Rojas et al, 2014;Benincasa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%